Unitarity and the Vainshtein mechanism - Kaloper, Nemanja; Padilla, Antonio; Saffin, Paul M.; Stefanyszyn, David (American Physical Society, 2015)
We investigate low energy limits of massive gauge theories that feature the Vainshtein mechanism, focussing on the effects of the UV modes that are integrated out. It turns out that the Goldstone sectors are significantly influenced by the effects from such modes relative to the effective field theories where the irrelevant operators induced by heavy modes are simply cast aside. The effects of the consistently retained higher order corrections affect the strong coupling and show that the nature of the UV completion influences the low energy theory significantly. This casts doubts on the naively estimated environmental strong coupling scale, and on the effectiveness of the environmental enhancement of screening. The environmental effects by themselves might not suffice to cure the bad behavior of the theory beyond the vacuum cutoff.